Attributes that Generation Y business students desire in an employee value proposition in management consulting in South Africa - Bhoola, Kavir (My University, 2014)
Attracting talented individuals to management consulting firms within a competitive market remains a challenge for many firms. In an environment where a large amount of Generation Y individuals are entering the workplace, tailoring an employee value proposition (EVP) to meet the needs of the market is one of the means of attracting talented individuals to an organisation. This research investigated the attributes that Generation Y business students desire in the EVP of management consulting firms. It also investigated if there is a link between the Generation Y characteristics and selection of EVP attributes. A quantitative approach using surveys was undertaken on 158 students pursuing postgraduate business studies. A qualitative approach with eight experienced management consulting professionals was also undertaken. The findings suggest that „compensation‟, „development opportunities‟, „future career opportunities‟ and „work-life balance‟ are the most desired EVP attributes. Furthermore, there is evidence that Generation Y characteristics are linked to the selection of desirable EVP attributes. The findings of the research are consistent with existing literature on the subject of EVP, despite the differences in age group, geography and target industry.
MBA thesis
Keywords: Generation Y; Employee value propositions; Consultants